PENGUJIAN PECKING ORDER HYPOTHESIS MELALUI KETERKAITAN DIVIDEND PAYOUT RATIO, FINANCIAL LEVERAGE DAN INVESTMENT OPPORTUNITY - Yuharningsih Yuharningsih (Jurnal Keuangan dan Perbankan, 2008)
This study is aimed to examine the prediction of Pecking Order hypothesis inIndonesia by relationship between dividend payout ratio, financial leverage and investmentopportunity. The Pecking Order hypothesis indicates there is negative relationship betweendividend payout ratio and investment opportunity. The dividend payout ratio determinantsare financial leverage, investment opportunity, cashflow, earnings and growth of sale. Thefinancial leverage determinants are dividend payout ratio, investment opportunity, earnings,size and growth of sale. The investment opportunity determinants are dividend payout ratio,financialo leverage, earnings, assets structure and Q ratio. The data is collected from 28manufacturing is listed in Jakarta Stock Exchange for the period 2000 2004. Analize of Thesimultaneous equation model is used computer statistic program; Generall Method of Moment(GMM) technics. These result imply that the have relationship simultans of dividend payoutratio, financial leverage and investment opportunity but no significant evidence thatmanufacturing companies in Indonesia tend to follow the Pecking Order hypothesis. In additionthat dividend payout ratio and investment opportunity gives positif and significant influence,financial leverage and investment opportunity gives negative and significant influence, financialleverage gives positif and significant influence on dividend payout ratio but divedend payoutratio no significant influence on financial leverage.